2014
DOI: 10.1016/j.tranpol.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The safety challenge of increased cycling

Abstract: Many countries have recently set out policy frameworks to support the growth of cycling. However, increased cycling can mean more collisions, injuries and even fatalities. This paper discusses the role of safety in cycling policy in the particular case of Ireland, which is one of the countries that has a government-endorsed policy to increase cycling. It examines available information on cycling, including police-reported accident data over the last fifteen years and more recent hospital accident data. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
1
18
0
2
Order By: Relevance
“…Code V182 has over 1,500 cases and it seems strange that coders are unsure whether the person was a cyclist or a passenger but were sure that it was not a traffic accident. (Short and Caulfield, 2014). Similar problems with coding traffic and non-traffic accidents were found in Kudryavtsev et al (2013) Moreover, in the record linkage results described in Section 4, some of these supposedly non-traffic accidents are matched with police recorded crashes.…”
Section: Hospital Datasupporting
confidence: 55%
See 1 more Smart Citation
“…Code V182 has over 1,500 cases and it seems strange that coders are unsure whether the person was a cyclist or a passenger but were sure that it was not a traffic accident. (Short and Caulfield, 2014). Similar problems with coding traffic and non-traffic accidents were found in Kudryavtsev et al (2013) Moreover, in the record linkage results described in Section 4, some of these supposedly non-traffic accidents are matched with police recorded crashes.…”
Section: Hospital Datasupporting
confidence: 55%
“…As argued by Short and Caulfield (2014), this is evidence of a weakness in cycling policy because the official data seriously understate the risks involved. Car occupants provide a different example.…”
Section: Linkage Variablesmentioning
confidence: 99%
“…The uncertainty surrounding police records for non-fatal casualties has already been mentioned with respect to police under-reporting in Ireland (Short and Caulfield, 2014). A wider issue is whether riskiness is well measured by the number of incidents that result in police reports or hospitalisations at all.…”
Section: When Are Bicycle Crashes Most Likely?mentioning
confidence: 99%
“…A recent comparison of hospital and police records of casualties from cycling in Ireland suggests that underreporting may lead to underestimates of the true risks of cycling (Short and Caulfield, 2014). This issue is especially pertinent to the present paper, which uses the publicly available STATS19 dataset, collated by the police.…”
Section: Introductionmentioning
confidence: 98%
“…Short and Caulfield (2014) demonstrated that cycling in the city is not as safe as some of the statistics report and that for the total number of days spent in hospital per transport accident for cyclists are over 13% of total days spent in hospital (in 2011), while cycling modal share of approximately 5% in 2011. Figure 1 shows that the number of cyclist deaths in Dublin City had been gradually decreasing since 2005.…”
Section: Introductionmentioning
confidence: 94%